Dual antiplatelet therapy for 1 versus 3 months in high bleeding risk patients with or without oral anticoagulant therapy after coronary stenting. (3rd October 2022) - Cao, D; Mehran, R; Sartori, S; Spirito, A; Snyder, C; Valgimigli, M
Abstract: Background: A short DAPT duration after coronary stenting has been associated with similar ischemic outcomes and fewer bleeding complications in patients at high bleeding risk (HBR). Whether these effects are preserved irrespective of concomitant oral anticoagulant (OAC) therapy remains unclear. Purpose: To evaluate the safety and efficacy of 1-month versus 3-month DAPT among HBR patients with or without indication to OAC therapy who undergo cobalt-chromium everolimus-eluting stent implantation. Methods: The XIENCE Short DAPT Program comprises three prospective, international, single-arm studies evaluating 1-month (XIENCE 28 USA and Global) or 3-month (XIENCE 90) DAPT in HBR patients who had undergone successful everolimus-eluting XIENCE stent implantation. OAC therapy at discharge was a study inclusion criterion. Subjects were eligible to discontinue DAPT at 1 or 3 months if free from ischemic events and adherent to DAPT. The primary endpoint was the composite of all-cause death or any myocardial infarction (MI). The major secondary endpoint was Bleeding Academic Research Consortium (BARC) type 2–5 bleeding. In this exploratory analysis, HBR patients on 1-month DAPT were compared with those on 3-month DAPT according to the presence of background OAC therapy. Ischemic and bleeding outcomes were assessed between 1 and 12 months after index PCI using propensity-score (PS) adjustment. Results: A total of 3, 364 patients, 1, 392 on 1-month DAPT and 1, 972 on 3-month DAPT, were eligible for the analyses. Patients on OAC therapy (n=1424, 42.3%) were younger, more often male and of white race, and with a lower prevalence of other HBR criteria such as chronic kidney disease and anemia. The incidence of death or MI at 12 months was similar between the two groups (8.0% vs 7.9%) while BARC 2–5 bleeding was higher in OAC patients (12.2% vs 7.2%). After PS adjustment, 1-month DAPT, compared with 3-month DAPT, did not increase the 1-year risk of death or MI in both OAC (adjHR 0.71, 95% CI 0.47–1.08) and non-OAC patients (adjHR 1.24, 95% CI 0.88–1.75; p-interaction = 0.11). The risk of BARC 2–5 bleeding was consistently reduced in both OAC (adjHR 0.71, 95% CI 0.51–1.00) and non-OAC patients (adjHR 0.77, 95% CI 0.53–1.11; p-interaction = 0.69). Conclusions: Among HBR patients undergoing everolimus-eluting stent implantation, 1-month DAPT compared with 3-month DAPT was associated with similar ischemic outcomes and reduced bleeding, regardless of concomitant OAC therapy. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Abbott